Jabrayilova, Zarifa - (:unkn) unknown (My University, 2025)
Zarifa Gasim gizi Jabrayilova was born in 1961. In 1984, she graduated from the “Automatics and Computing” faculty of the Azerbaijan Polytechnic Institute named after Ch. Yildirim with a diploma of honors. In 1984, she was appointed to the Department of Automated Control Systems of the Azerbaijan Academy of Sciences. In 2018, she was elected as the Chairwoman of the Institute's Women's Council. Since 2021, she has been the Scientific Secretary of the Problem Council on Physical, Mathematical and Technical Sciences of the Council for the Coordination of Scientific Research of the Republic of Azerbaijan. In 2015, she was awarded the Honorary Decree of the Department of Physical, Mathematical and Technical Sciences of ANAS for her long-term scientific and scientific-organizational activities. In 2021, on the occasion of her 60th anniversary, she was awarded the Honorary Decree of the Institute of Information Technologies of ANAS for her fruitful scientific and practical activities in the field of information technologies.